Analisis Kualitas Informasi Akuntansi Terhadap Akuntabilitas Internal, Evaluasi Kinerja Keuangan, dan Pengambilan Keputusan Keuangan Pada Badan Pendidikan dan Pelatihan Keuangan - Acwin Hendra Saputra (Pusat P2M Politeknik Negeri Batam, 2020)
This study aims to determine the effect of the quality of accounting information on internal accountability, financial performance evaluation, and financial decision making in work units within the BPPK. The total number of respondents in this study were 116 people. This research uses quantitative methods with causal relationships and inferential analysis, and the type of data produced is primary data. The results of the study conclude that the quality of accounting information has a significant positive relationship with internal accountability at the BPPK, the quality of accounting information has a significant positive relationship with the BPPK's financial performance evaluation, the quality of accounting information has a significant positive relationship with financial decision making at the BPPK. The quality of BPPK accounting information has a high and unidirectional correlation with internal accountability, moderate and unidirectional correlation with financial performance evaluation, and moderate and unidirectional correlation with financial decision making.